Kompetensi Pustakawan di Era Industri 4.0 dalam Menghadapi Information Overload - Hariyati, Mutty; Heriyanto, Heriyanto (Daluang: Journal of Library and Information Science, 2021)
Introduction: The phenomenon of information overload experienced by the Indonesian people has caused many problems ranging from a decrease in the level of public awareness in understanding the validity and accuracy of information sources to changes in public information behavior. One of the problems in the flood of information is the increase of publications both scientific and popular which are the daily consumption of society which is very relevant to the librarian in the current situation and in the future.Methodology: This research was conducted qualitatively by collecting data from literatures that relevant to the research theme. The collected data was then identified to find patterns that match the research objectives, namely to find out the competence of librarians that is relevant for the industrial era 4.0.Discussion: The results show librarians need to have strategies in developing new ways to help people direct and focus their search for finding documents or information that are accurate and valid.Conclusion: It is known that the information overload phenomenon is one of the hallmarks of this industrial 4.0 era so that it requires the development of librarian competencies in maintaining their contribution and existence in the information society.